2005
DOI: 10.1039/b509003b
|View full text |Cite
|
Sign up to set email alerts
|

A green process for chlorine-free benzaldehyde from the solvent-free oxidation of benzyl alcohol with molecular oxygen over a supported nano-size gold catalyst

Abstract: Benzyl alcohol is oxidized selectively to benzaldehyde with high yield, with a little formation of benzylbenzoate, by molecular oxygen over a reusable nano-size gold catalyst supported on U 3 O 8 , MgO, Al 2 O 3 or ZrO 2 in the absence of any solvent.Liquid phase oxidation of benzyl alcohol is an important preferred reaction practically for the production of chlorine-free benzaldehyde, without loss of carbon in the form of CO 2 (a geenhouse gas). The preparation of benzaldehyde by reacting benzyl alcohol with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(111 citation statements)
references
References 19 publications
(4 reference statements)
0
99
1
Order By: Relevance
“…amount of gold deposited), average particle size and distribution of particle size of the gold deposited on support were found to be strongly dependent upon the method of gold deposition (viz. impregnation, co-precipitation, DP and HDP) and metal oxide support used in the supported gold catalysts [37,[45][46][47][48][49][50][51][52][53]. The Au particle size and its distribution in the catalyst were also strongly influenced by the calcination temperature [52,65,66], whereas the presence of different surface Au species depends upon the support used in the gold catalysts [37,46,48,[67][68][69].…”
Section: Factors Influencing Gold Deposition Au Particle Size and Sumentioning
confidence: 99%
See 3 more Smart Citations
“…amount of gold deposited), average particle size and distribution of particle size of the gold deposited on support were found to be strongly dependent upon the method of gold deposition (viz. impregnation, co-precipitation, DP and HDP) and metal oxide support used in the supported gold catalysts [37,[45][46][47][48][49][50][51][52][53]. The Au particle size and its distribution in the catalyst were also strongly influenced by the calcination temperature [52,65,66], whereas the presence of different surface Au species depends upon the support used in the gold catalysts [37,46,48,[67][68][69].…”
Section: Factors Influencing Gold Deposition Au Particle Size and Sumentioning
confidence: 99%
“…0.1 g catalyst, temperature = 130°C, pressure = 1.5 atm, and reaction time = 5 h) [51]. Among the supported nano-gold catalysts ( .…”
Section: Solvent-free Benzyl Alcohol Oxidation By Molecular Omentioning
confidence: 99%
See 2 more Smart Citations
“…Among the various reactions, selective oxidation of alcohols with or without solvents with supported gold nanoparticles has grabbed considerable attention due to their higher selectivity and lower susceptibility to leaching [23][24][25][26][27][28]. Moreover, it has been shown that the choice of a suitable metal oxide as support plays a crucial role in determining the catalytic activity and selectivity of the gold catalysts [29].…”
Section: Introductionmentioning
confidence: 99%